1999
DOI: 10.1046/j.1523-1755.1999.0550031019.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of 1,25-dihydroxyvitamin D, 24,25-dihydroxyvitamin D, and 25-hydroxyvitamin D in nondialyzed patients with chronic renal failure

Abstract: These results suggest that hypoalbuminemia and the presence of DM independently affect serum 25(OH)D levels, probably via diabetic nephropathy and poor nutritional status associated with diabetes, and that 25(OH)D is actively catalyzed to 24,25(OH)2D in CRF, probably largely via extrarenal 24-hydroxylase. Serum levels of 1,25(OH)2D were significantly affected by the degree of renal failure. Thus, this study indicates that patients with CRF, particularly those with DM, should receive supplements containing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
142
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(166 citation statements)
references
References 55 publications
18
142
0
6
Order By: Relevance
“…However, it is likely that most patients not receiving treatment with active vitamin D for SHPT were 1,25(OH) 2 D deficient. In general, serum levels of 1,25(OH) 2 D decrease as renal mass declines, with serum concentrations of 1,25(OH) 2 D reported to be positively correlated with GFR [39] and creatinine clearance [40][41][42]. Nevertheless, we acknowledge that variability in extrarenal 1,25(OH) 2 D production make it impossible to assume that 1,25(OH) 2 D deficiency is present in every ESRD patient not treated with active vitamin D. However, potential misclassifications from inclusion of patients recently treated with vitamin D derivatives and patients who may not be vitamin D deficient in the nonvitamin D-receiving group would tend to minimize rather than accentuate associations between active vitamin D treatment and muscle strength and size.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that most patients not receiving treatment with active vitamin D for SHPT were 1,25(OH) 2 D deficient. In general, serum levels of 1,25(OH) 2 D decrease as renal mass declines, with serum concentrations of 1,25(OH) 2 D reported to be positively correlated with GFR [39] and creatinine clearance [40][41][42]. Nevertheless, we acknowledge that variability in extrarenal 1,25(OH) 2 D production make it impossible to assume that 1,25(OH) 2 D deficiency is present in every ESRD patient not treated with active vitamin D. However, potential misclassifications from inclusion of patients recently treated with vitamin D derivatives and patients who may not be vitamin D deficient in the nonvitamin D-receiving group would tend to minimize rather than accentuate associations between active vitamin D treatment and muscle strength and size.…”
Section: Discussionmentioning
confidence: 99%
“…3 According to the target levels, the prevalence of 25OHD deficiency and insufficiency in this population is high, namely 70% to 80%, regardless of geographic location. 4,5 Kidney graft recipients have various degrees of renal functional impairment with increased levels of parathyroid hormone (PTH). In several reports vitamin D status has been investigated.…”
mentioning
confidence: 99%
“…1,2 Observations have shown that CKD is associated with the high incidence of vitamin D deficiency. 23 Vitamin D in the chronic renal disease 86% of the patients, and that the functional meaning of this finding is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…1 In another analysis involving 76 Japanese patients with CKD, serum levels of 25(OH)D were associated with hypoalbuminemia, diabetes mellitus and serum phosphorus, but no correlation was found between serum levels of 25(OH)D and creatinine clearance of the patients. 2 In these studies, 25(OH) D insufficiency and deficiency have also been associated with the presence of hyperparathyroidism during CKD, which leads to the evaluation of the levels of this vitamin in patients with CKD and hyperparathyroidism; if the value of 25(OH)D is lower than 30 ng/mL, it is replaced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation